Potensi Ekstrak Etil Asetat Batang Bajakah Tampala sebagai Tabir Surya - Wulandari, Erna Tri; Bungadea, Dominica; Cholisna, Rizka Sauqi (JFIOnline | Print ISSN 1412-1107 | e-ISSN 2355-696X, 2025)
Currently, natural ingredients are widely used as raw materials for sunscreen. Bajakah Tampala stem (Spatholobus littoralis Hassk) contains phenolic compounds, especially flavonoids.  Flavonoids have chromophore groups that can absorb ultraviolet (UV) A and ultraviolet (UV) B and capture free radical due to exposure to UV and can be dissolved by ethyl acetate. This study aims to examine the potential of ethyl acetate extract from Bajakah Tampala stems as a sunscreen in vitro by measuring the SPF (Sun Protection Factor) value and antioxidant activity as well as total phenolic content, especially flavonoids. The research began with the extraction of Bajakah Tampala stem powder using the soxhletation method, then the SPF value of the dry extract was measured using the UV-Vis spectrophotometric method. Antioxidant activity was tested using the DPPH (2,2-diphenyl-1-picrylhydrazyl) method. The Folin-Ciocalteau method was used to determine total phenolic content (mg gallic acid equivalents [GAE] per gram of extract [mg GAE/g]). Total flavonoid content was measured colorimetrically with AlCl3 reagent (mg quercetin equivalents [QE] per gram of extract [mg QE/g]). In this study, it was found that Bajakah stem extract contained total phenols of 51.73 mg GAE/g extract, total flavonoids of 17.91 mg QE/g extract, an SPF value of 5.53 and had antioxidant activity with an IC50 value of 159.17 μg/mL. Bajakah Tampala stem ethyl acetate extract has potential as a sunscreen because it contains phenols, especially flavonoids and antioxidant properties.